A MRCC study of the isomerisation of cyclopropane. (17th November 2017) - Lang, Jakub; Švaňa, Matej; Demel, Ondřej; Brabec, Jiri; Kedžuch, Stanislav; Noga, Jozef; Kowalski, Karol; Pittner, Jiří
ABSTRACT: Mukherjee's and Brillouin-Wigner multi-reference coupled cluster methods with universal state selective (USS) corrections were used to study the isomerisation of cyclopropane to propene through a trimethylene/propylidene diradicals. Main aim was to obtain high quality ab-initio data using advanced methods that treat both static and dynamic correlation in the involved species, however, we also report implementation of the diagonal USS correction in the LPNO-MRCC code and its performance assessment. The MkCCSD(T)/cc-pV5Z lower bound of interaction energy of cyclopropane isomerisation via trimethylene is 65.6 kcal/mol (59.9 kcal/mol with ZPVE correction), in a good agreement with experimental values in the range 60–65 kcal/mol. The MkCCSD(T)/cc-pV5Z adiabatic singlet-triplet gap in trimethylene is 0.6 kcal/mol, slightly higher than previous CASPT2 result −0.7 kcal/mol by Skancke et al. Abstract :